Mothers, Medicine, and Monstrosities: Historicizing Childbirth and Contraception in Nora Jaffary’s Reproduction and Its Discontents — A View from Río Frío - French, William (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2018)
Written as the author’s contribution to a roundtable held at the Canadian Historical Association’s annual conference in Regina on Nora Jaffary’s, Reproduction and Its Discontents in Mexico: Childbirth and Contraception from 1750 to 1905, recipient of the 2017 Ferguson prize, the article utilizes a popular nineteenth century Mexican novel, Los bandidos de Río Frío, as a lens through which to reflect upon childbirth, the construction of various systems of medical knowledge, contraception, virginity, monstrosities, the written word, and national imagining in Jaffary’s book. Both authors see a close connection between childbirth and the project of nation building in Mexico: Payno, to foreground the importance of inheritance, and Jaffary, to stress the ways in which laws, learning, institutions, and traditions shaped reproduction and its outcomes. Notable in Jaffary’s work is the eschewing of traditional periodizations of Mexican history in favour of the testing of hypotheses and a focus on the agency of women. Also compelling is Jaffary’s interest in the emergence of the discursive category of the “general public,” a construct that links her work to that of others interested in the “lettered city.”